The Jurisdiction of Civil Servants of The POM Agency in Investigating Drug and Food Circulation Crimes in Indonesia. - Bariyah, Khoirotul (Jurnal Legisci, 2024)
Health growth has a crucial role in enhancing the quality of socially and economically productive individuals. By achieving optimal levels of public health, health advancement plays a crucial role in promoting economic growth and reducing poverty. The community's health and nutrition status is being enhanced through various initiatives, such as enhancing access to high-quality and inexpensive healthcare services, providing necessary healthcare resources, and empowering the community to participate in healthcare efforts actively. This study underscores the pivotal role of Civil Servants of the POM Agency in addressing drug and food circulation offenses, aiming to eliminate any violations of the Health Law restrictions in this regard. Investigation, as defined by this Law, is the systematic process conducted by investigators to search for and gather evidence to shed light on criminal acts and identify the culprit.